Appraisal of Ni Species Supported on Porous MgO during Ethanol Steam Reforming by XAS - Possato, Luiz G. [UNESP]; Pulcinelli, Sandra H. [UNESP]; Martins, Leandro [UNESP]; Briois, Valerie; Santilli, Celso V. [UNESP] (Wiley, 2022)
Operando time-resolved X-ray absorption spectroscopy (XAS) was used to determine nickel species supported on porous MgO during the ethanol steam reforming reaction. The Principal Component Analysis (PCA) of the nickel K-edge XAS spectra revealed Ni(OH)2, NiMgO, and metallic Ni during the activation and reaction of the catalysts. The Multivariate Curve Resolution-Alternating Least Squares (MCR-ALS) method for the time-resolved XAS spectra data permitted to calculate the concentration of species during the activation and reaction steps and to determine the formation of NiMgO and nickel reduction degree. The samples prepared with surfactants, Ni10MgO-F127 and Ni10MgO-P123, showed less nickel reduction (less than 30 %) but were more active and stable than the reference Ni10MgO catalyst, which reduced 52 %. It happened due to the smaller particle size and a larger specific area of the porous supports. The samples synthesized without Pluronic deactivated, and ethanol dehydrogenation became predominant instead of the ethanol steam reforming.
Keywords: ethanol steam reforming; hydrogen; MgO; nickel; Time-resolved XAS